Increasing cytochrome P450 enzyme diversity by identification of two distinct cyclodipeptide dimerases - Liu, Jing; Xie, Xiulan; Li, Shu-Ming (Chemical communications (Cambridge, England), 2020)
Genome mining revealed the presence of two cdps-p 450 operons in Saccharopolyspora antimicrobica . Heterologous expression, biochemical characterisation and structure elucidation proved that the two P450 enzymes catalyse distinct regio- and stereospecific dimerizations of cyclo -( l -Trp- l -Trp), which significantly expands the repertoire of diketopiperazine-tailoring enzymes. TtpB1 connects the monomers via C3-C3′, both from the opposite side of H-11/H-11′, while TtpB2 is characterised as the first P450 to mainly catalyse the unusual linkage between N1′ and C3 from the H-11 side. Two P450 enzymes were characterised to catalyse distinct regio- and stereospecific dimerizations of cyclo -( l -Trp- l -Trp), differing from those previously reported in actinobacteria.